2019
DOI: 10.1007/s00066-019-01480-3
|View full text |Cite
|
Sign up to set email alerts
|

PET/MRI-guided GTV delineation during radiotherapy planning in patients with squamous cell carcinoma of the tongue

Abstract: Purpose The aim of the study was to evaluate the usefulness and accuracy of 18-fluorine-labeled fluorodeoxyglucose (PET) and magnetic resonance imaging (MRI) hybrid in gross tumor volume (GTV) delineation during radiotherapy planning in patients with carcinoma of the tongue. Methods Ten patients with squamous cell carcinoma (SCC) of the tongue underwent computed tomography (CT) and PET/MRI examination. The GTV for primary tumor and lymph nodes (nGTV) were defined on CT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 35 publications
3
23
0
3
Order By: Relevance
“…PET complements anatomical imaging modalities, particularly in tumor volume determination. Therefore, our study demonstrated stronger correlations between SUV values and PET/MRI than between those values and CT [29]. Tumor volume and SUV values are considered prognostic factors-increased values of both are associated with a higher risk of death [30,31].…”
Section: Discussionmentioning
confidence: 50%
“…PET complements anatomical imaging modalities, particularly in tumor volume determination. Therefore, our study demonstrated stronger correlations between SUV values and PET/MRI than between those values and CT [29]. Tumor volume and SUV values are considered prognostic factors-increased values of both are associated with a higher risk of death [30,31].…”
Section: Discussionmentioning
confidence: 50%
“…Furthermore, 18 F-fludeoxyglucose positron emission tomography/computed tomography (FDG-PET/CT) is often performed in order to rule out distant metastases before starting curative treatment. Because FDG-PET/CT has also demonstrated promising sensitivity, specificity, and accuracy regarding the detection of lymph node metastases as well as the detection of the primary tumor [ 10 , 11 ], implementation of PET into the radiation planning process might change the resulting target volumes, as it has already been demonstrated for other tumor entities like prostate cancer or squamous cell cancer of the tongue [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…First, while in 17 of 18 patients of our study cohort the target volume was defined by the extension of the MIBG-active lesion at the time of RT, previous studies defined the target volume as the volume visible on cross-sectional studies either at initial staging or after induction chemotherapy. Due to these diverging approaches resulting in different target volumes, the comparison of data remains challenging [18][19][20]. There were no general recommendations for the irradiation of metastases within NB 97 and NB 2004 and the indication for RT to metastatic lesions was based on individual decisions, forming a risk for selection bias [21].…”
Section: Discussionmentioning
confidence: 99%